Infection of marmosets with parainfluenza virus types 1 and 3. - Hawthorne, J D (1982)
Infection of wild marmosets (Saguinus mystax) with strains of parainfluenza virus types 1 and 3 resulted in acute respiratory infection. Virus replication in the upper respiratory tract was of a degree similar to that seen in children acutely infected with parainfluenza viruses. Serum antibody developed with both virus types; however, local secretory antibody was not detectable. The infection was transmissible to susceptible animals up to 3 days inoculation of the primary animal.